PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA BARBERSHOP KEEP HANDSOME DI CIPAYUNG DEPOK - Makmur, Pramudi; Ivantan (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of Price and Service Quality on Customer Satisfaction of Keep Handsome Barbershop in Cipayung Depok, both partially and simultaneously. The method used is a quantitative method. By sampling using the slovin formula technique obtained by the sample in this study amounted to 97 respondents. Analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis tests. The results of this study Price has a significant effect on consumer satisfaction with the regression equation Y = 32.076 + 0.188 (X1). Test the hypothesis obtained t count (7.604) > t table (1.661), thus Ho1 is rejected and Ha1 is accepted. This means that Price has a significant effect on Consumer Satisfaction. Service Quality has a positive and significant effect on customer satisfaction with the regression equation Y = 29,428 + 0.250 (X2). Test Hypothesis obtained t count t count (8.841) > t table (1.661). thus Ho2 is rejected and Ha2 is accepted, meaning that there is a significant influence on Service Quality affecting Customer Satisfaction. Price and Quality of Service to Customer Satisfaction with regression equation Y = 28,324 + 0.105 (X1) + 0.177 (X2), f count (53,175) > f table (3,093) and sig value (0.000) < 0.05). So it was concluded that there was a positive and significant influence of X1 Price and X2 Service Quality variables simultaneously on Y Consumer Satisfaction so that Ho3 was rejected and Ha3 was accepted.